Objektive Bewertung querdynamischer Reifeneigenschaften im Gesamtfahrzeugversuch - Gutjahr, David (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
Tire properties show significant impact on the driving behavior of a modern passenger car. Today tires are being optimized in their driving function and adapted to the vehicle in close cooperation by vehicle and tire manufacturers. To meet all requirements, support of the test drive engineers by a tire test system based pre-selection, with help of a virtual evaluation method, becomes necessary. Therefore the root cause between driver, vehicle and tire characteristics has been examined.